Trophobiotic interactions between mealybug and ants in western Mediterranean basin [Dataset] - Plata, Ángel (Instituto Valenciano de Investigaciones Agrarias (IVIA), 2023)
This study was carried out in 17 persimmon orchards from western Mediterranean basin, the main persimmon producing area from the Mediterranean Basin. Nine trees were sampled per plot in spring (between May 10 and 22), summer (between July 14 and July 27) and early-autumn (between September 27 and October 10) across two consecutive years (2020 and 2021). For each tree, sampling season and year, 120 leaves (30 per cardinal direction), 40 fruits (10 per cardinal direction) and the surface of the trunk (from the base to a 50 cm height) were surveyed. All mealybugs and ants were identified down to species level and counted, as well as the number of the long-tailed mealybug P. longispinus per developmental stage (instar). Additionally, the number of parasitized P. longispinus was recorded from all the individuals surveyed, and we also registered the abundance of potential predators of P. longispinus. The data set contains a CSV file that includes the raw data collected in the study (i.e., per sampling unit). A legend is included to facilitate the interpretation of the data.